The Effect of the Cooperative Course Review Hooray Learning Model on Students’ Learning Outcomes - Sezh Faheem; Dabuos Uzeir; Baliwal Yacub (Journal La Edusci, 2021)
This study aims to investigate the effect of Cooperative Course Review Horay learning model on students learning outcome. The study uses true experimental design. Description: This research will use descriptive and inferential statistics to quantitatively analyze learning outcomes, with the latter being the primary method of analysis. To describe the scores of the research sample for each variable, a descriptive statistical analysis was carried out to determine their distribution. The findings indicate that Cooperative Course Review is beneficial. The Horay learning method provides great outcomes in terms of student learning. Despite the fact that the average score for the experimental group is 85.20 points, it is the median score for the experimental group that stands at 90 points. The control class has a standard deviation of 62.80 points and a median of 60.00 points, both of which are positive values